Impact of Ni alloying on Fe-C martensite ageing: an atomistic investigation. (December 2021) - Eyméoud, Paul; Huang, Liangzhao; Maugis, Philippe
Highlights: Computational investigation combining first-principles and Kinetic Monte-Carlo approaches. Ni alloying lowers migration energies and force dipole tensor components associated to an interstitial C in α -Fe. Ni alloying accelerates ageing kinetics. Graphical abstract: Abstract: We propose a computational investigation of Ni-alloying impact on Fe-C martensite ageing, at the atomic scale. Using the Climbing Image Nudged Elastic Band technique, we showed the repulsive nature of Ni-C pairwise interactions in α -iron, and demonstrated that Ni alloying lowers the migration energies and force dipole tensor components associated to an interstitial carbon in α -iron. Computed values of pairwise interactions, migration energies and dipole components were used to implement a Kinetic Monte-Carlo approach. We found that Ni alloying: (i) has negligible impact on martensite thermodynamical stability, (ii) accelerates ageing kinetics, by increasing carbon diffusivity.